we have three points so we use second polynomial fitting like that
"p(x) = a + bx + c^2"
the points are (2, 4); (3, 6) and (5, 10).
"y_1 =" "ax_1^2 + bx_1+c"
"y_2 = ax_2^2 + bx_2 + c"
"y_3 = ax_3^2 + bx_3 + c"
The task is to find a, b and c. Start by substituting each of the points into the equation, we have
4 = a(2)2 + b(2) + c;
6 = a(3)2 + b(3) + c;
10 = a(5)2 + b(5) + c;
We can write this more compactly as a matrix equation
"\\begin{bmatrix}\n 4&2&1\\\\\n 9&3&1\\\\\n25&5&1\n\\end{bmatrix}" "\\begin{bmatrix}\n a\\\\\nb\\\\\nc\n\n\\end{bmatrix}" = "\\begin{bmatrix}\n 4\\\\\n 6\\\\\n10\n\\end{bmatrix}"
Or we use Cramer's rule for:
4a + 2b + c = 4
9a + 3b + c = 6
25a + 5b + c = 10
D = "\\begin{bmatrix}\n 4&2&1\\\\\n 9&3&1\\\\\n25&5&1\n\\end{bmatrix}"= (4*3*1 + 2*1*25 + 1*9*5) - (25*3*1 + 5*1*4 + 1*9*2) = -6;
Dx = "\\begin{bmatrix}\n 4&2&1\\\\\n 6&3&1\\\\\n10&5&1\n\\end{bmatrix}" = (4*3*1 + 2*1*10 + 1*6*5) - (10 * 3 *1 + 5*1*4 + 1*6*2) = 0;
x = "\\frac{D_x}{D} = \\frac{0}{-6} = 0"
Dy = "\\begin{bmatrix}\n 4&4&1\\\\\n 9&6&1\\\\\n25&10&1\n\\end{bmatrix}" = (4*6*1 + 4*1*25 + 1*9*10) - (25*6 + 10*1*4+1*9*4) = -12
"b = \\frac{D_y}{D} = \\frac{-12}{--6} = 2"
D"_z = \\begin{bmatrix}\n 4&2&4\\\\\n 9&3&6\\\\\n25&5&10\\end{bmatrix}" = 0
"c = \\frac{D_z}{D} = \\frac{0}{-12} = 0"
4 + c = 4 -> c = 0;
y = 2x
Comments
Leave a comment